Performance Evaluation of Apple Varieties at Wadla District, North Wollo, Ethiopia - Abtew, Yimam Ali; Kassaye, Solomon; Semawu, Fentawu (Agro Bali : Agricultural Journal, 2025)
Apple is one of the most important fruit crops in the highland areas of Ethiopia. This fruit tree is the only producible fruit tree in the highlands of North Wollo. However, its productivity is very low compared to other countries particularly that of temperate regions. This is partly attributed to lack of adaptable, high yielding and better quality apple varieties to farmers. To solve this problem apple variety trial was carried out at Wadela District from 2012-2019. The trial was laid out in randomized complete block design with three replications. Low to medium chill grafted apple seedlings were planted at a spacing of 3.0 m between rows and 3.0m between plants. Each plot was planted with three seedlings. On average irrigation water was applied on 7 days interval. Necessary plant protection and agronomic practices like training and pruning were applied as required. Scion diameter, rootstock diameter, girth ratio, canopy diameter, plant height, mean fruit weight and fruit yield data were collected for two consecutive years. Yield data was collected two times within a year. The Anna variety gave significantly the highest fruit yield (9.52 t. ha-1) followed by Gransmith (8.92 t .ha-1). On the other hand, Crispin gave the lowest fruit yield (7.77 t .ha-1). Fruit yield obtained by Anna and Gransmith were higher by 23% and 15%, respectively, compared to the lowest yielding variety, Crispin. Similarly, Anna and Gransmith also gave significantly the highest mean fruit weights of 85.98 and 62.34 g, respectively, as compared to the variety Crispin, which gave a mean fruit weight of 41.01 g. Farmers also select Anna variety by their criteria setted. Therefore, Anna and Gransmith are recommended for producers at Gashena conditions and similar agro-ecologies.